Architectural landscape in the Jewish autonomous region - Ivanova, Alina; Kovalevsky, Andrey (project baikal, 2021)
The article is based on the field studies carried out in 2018-2019. The authors tried to find assimilation of Jewish culture inside the experimental space of the Soviet period. However, after coming to the conclusion that the development of the settlements of the Jewish autonomous region had ‘international’ features, they turned their focus on the description of vernacular architecture (individual low-storey housing, customized governmental accommodation facilities in the form of barracks, etc.). The attempt to comprehend the specific features of the development of the artificially designed territory of the settlements with national Jewish colour in the context of Soviet industrial colonization of the Far East is an important key to understanding the regional identity and preservation of cultural heritage.
Keywords: vernacular architecture; Far Eastern barracks; wooden architecture; frontier; Far East; colonization; cultural heritage